Relationship between obesity, sarcopenia, sarcopenic obesity, and bone mineral density in elderly subjects aged 80 years and over - Santos, Vanessa Ribeiro Dos; Christofaro, Diego Giulliano Destro; Gomes, Igor Conterato; Freitas Júnior, Ismael Forte; Gobbo, Luís Alberto (Sociedade Brasileira de Ortopedia e Traumatologia, 2018)
ABSTRACTObjective This study sought to analyze the relationship between the components and aggravations of body composition (obesity, sarcopenia, and sarcopenic obesity) and bone mineral density in elderly subjects aged ≥80 years.Methods A cross-sectional study design was utilized to assess 128 subjects aged between 80 and 95 years. Body composition and bone mineral density were measured by dual energy X-ray absorptiometry. Gait speed was assessment by walking test. The statistical analyses included Spearman's correlation, one-way analysis of variance, the chi-squared test, and binary logistic regression analysis.Results The elderly subjects with sarcopenia had lower bone mineral density compared to the obesity group, with higher risk for presence of osteopenia/osteoporosis in the spine (OR: 2.81; CI: 1.11–7.11) and femur (OR: 2.75; CI: 1.02–7.44). Obesity was shown to be a protective factor for osteopenia/osteoporosis in the spine (OR: 0.43; CI: 0.20–0.93) and femur (OR: 0.27; CI: 0.12–0.62).Conclusion It was found that lean mass is more directly related to bone mineral density (total, femur, and spine) and sarcopenia is associated with osteopenia/osteoporosis. Obesity represents a possible protective factor for osteopenia/osteoporosis in elderly subjects aged 80 years and over.

RESUMOObjetivo Analisar a relação entre os componentes e agravos da composição corporal (obesidade, sarcopenia e obesidade sarcopênica) com a densidade mineral óssea em idosos com idade ≥ 80 anos.Métodos Estudo com delineamento transversal que avaliou 128 sujeitos entre 80 e 95 anos. A composição corporal e densidade mineral óssea foram mensuradas por meio da técnica de absorciometria de raios X de dupla energia. A velocidade de caminhada foi avaliada pelo teste de caminhada usual. Para análise estatística foram feitos os testes de correlação de Spearman, análise de variância com um fator, teste qui-quadrado e análise de regressão logística binária.Resultados Os idosos com sarcopenia apresentaram valores menores de DMO quando comparados com o grupo obesidade com maior chance de risco para a presença de osteopenia/osteoporose na coluna (OR: 2,81; IC: 1,11-7,11) e fêmur (OR: 2,75 IC: 1,02-7,44). Obesidade apresentou fator de proteção para osteopenia/osteoporose na coluna (OR: 0,43; IC: 0,20-0,93) e fêmur (OR: 0,27; IC: 0,12-0,62).Conclusão Observou-se que a massa magra está diretamente relacionada com a DMO (total, fêmur e coluna) e que a sarcopenia está associada à osteopenia/osteoporose em idosos com 80 anos ou mais.
Relação entre obesidade, sarcopenia, obesidade sarcopênica e densidade mineral óssea em idosos com 80 anos ou mais
Keywords: Body composition; Osteoporosis; Aged 80 years and over; Composição corporal; Osteoporose; Idosos 80 anos ou mais